Value chains and nutrition: A framework to support the identification, design, and evaluation of interventions - Gelli, Aulo; Hawkes, Corinna; Donovan, Jason; Harris, Jody; Allen, Summer L.; de Brauw, Alan; Henson, Spencer; Johnson, Nancy L.; Garrett, James; Ryckembusch, David (International Food Policy Research Institute, 2015)
In this paper we explore how a value chain framework can inform the design of interventions for achieving improved nutrition. Conceptually, there are three main channels for value chains to improve nutrition: (1) through increased consumption of nutritious foods (a demand side pathway); or (2) through increased incomes from value chain transactions (a supply side pathway) or (3) through increased nutrition value-addition in the chain transactions. These three pathways are interlinked and involve complex dynamics that are not straightforward to understand.